Preparation process of solar cell composite electrode
The laser inclined groove is formed and the precursor material is filled with the precursor material, and the physical vapor deposition method is combined with the deposition of silver and copper, which solves the problems of insufficient utilization of the surface area and poor stability of the electrodes of traditional solar cells, and achieves efficient photoelectric conversion and long-term stability. Electrode performance.
Patent Information
- Application Number
- CN202411589536.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-21
AI Technical Summary
The planar design of traditional solar cell electrodes cannot fully utilize the surface area, limiting the contact area between the electrode and the silicon wafer, resulting in low photoelectric conversion efficiency, and metal electrode materials are easily affected by stress changes and external environment, resulting in aging and peeling of the electrode layer. The problem affects the long-term stability of solar cells.
Laser inclined grooves are used to form trenches with wide inside and narrow outside, and precursor material is filled in the grooves to form composite electrodes. The deposition of silver and copper is accurately controlled by physical vapor deposition (PVD), forming a composite electrode in the trapezoidal groove.
The contact area and conductivity of the electrode are improved, the contact resistance of the electrode is reduced, the current transmission efficiency is enhanced, and the mechanical strength and corrosion resistance of the electrode are improved through the combination of silver and copper, and the service life of the electrode is extended.
Smart Images

Figure CN119497441A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photovoltaic cells, and in particular to a preparation process of a solar cell composite electrode. Background Art
[0002] As an important device for clean energy conversion, solar cells have received extensive attention and research in recent years. Its core technology is to improve the photoelectric conversion efficiency and ensure long-term working stability. As an important component of solar cells, electrodes directly affect the photoelectric conversion efficiency and current collection capacity. Traditional solar cell electrodes mostly adopt a planar design, and metal electrodes are formed on the surface of the cell by screen printing or evaporation. Although these methods are mature, they still have certain technical limitations.
[0003] First, the planar design of traditional electrodes cannot fully utilize the surface area, which limits the contact area between the electrode and the silicon wafer, and thus limits the collection efficiency of charge carriers, resulting in low photoelectric conversion efficiency. In addition, metal electrode materials (such as silver and copper) are deposited on planar structures by conventional methods, which are easily affected by stress changes and the external environment, leading to problems such as aging and peeling of the electrode layer, thereby affecting the long-term stability of solar cells.
[0004] With the advancement of technology, laser etching has gradually become one of the key processes in solar cell manufacturing. Laser etching can form micro-nanoscale structures on the surface of silicon wafers through precise energy control, greatly improving the contact area of electrodes and the light absorption efficiency of devices. However, the existing laser etching process usually only forms a single vertical groove structure on the surface of silicon wafers, and its application is relatively limited, and it is difficult to achieve flexible control of the electrode shape.
[0005] To this end, we propose a preparation process for composite electrodes of solar cells. Summary of the invention
[0006] The present invention mainly solves the technical problems existing in the above-mentioned prior art and provides a preparation process of a solar cell composite electrode.
[0007] In order to achieve the above object, the present invention adopts the following technical scheme, a preparation process of a solar cell composite electrode, comprising the following steps: S1: Pretreatment of single crystal silicon wafers; S2: Laser inclined groove forming a groove that is wide inside and narrow outside; S3: Filling the precursor into the groove to form a composite electrode.
[0008] Preferably, in step 2, at least one group of tilted lasers is used to etch the monocrystalline silicon wafer on the opposite side, the laser tilt angle is set to 50°, the wavelength is 355nm, the pulse duration is in the picosecond level, the pulse frequency is set to 100kHz, the single pulse energy is 50μJ-200μJ, the focal length is adjusted to a focal diameter of 50μm-100μm, the target etching depth is 5 microns, and the scanning speed is initially set to 30 microns / s.
[0009] Preferably, the single crystal silicon wafer etched with the inclined groove is etched using a laser perpendicular to the single crystal silicon wafer, with a target depth of 4 microns and a width of 10 microns to generate a rectangular groove, which together with the inclined groove forms a trapezoidal groove.
[0010] Preferably, in step 3, the precursors are silver and copper, and the silver and copper are deposited in the grooves by physical vapor deposition to form a composite electrode.
[0011] Preferably, the precursor in step 3 is titanium dioxide gel, which is evenly scraped onto the trapezoidal grooves of the laser-etched single-crystal silicon wafer, and then burned to form a stable titanium dioxide electrode.
[0012] As a preferred method, the designed mask and the etched silicon wafer are fixed horizontally on a rotating fixture in the PVD equipment, and the pressure of the vacuum chamber of the PVD equipment is reduced to 10 −6 Torr, heat the substrate of the PVD equipment to 100°C-150°C, adjust the electron beam power of the electron beam evaporator to 5-10kW, and control the silver deposition rate to 2-10Å / s by monitoring the quartz crystal monitor to form a silver coating.
[0013] Preferably, after stopping silver evaporation, the evaporation source is switched to a copper target, the electron beam power of the electron beam evaporator is adjusted to 4-8kW, the deposition rate is maintained in the range of 2-10Å / s, and the substrate temperature of the PVD equipment is increased to 150°C-200°C.
[0014] Preferably, the laser-etched single crystal silicon wafer is cleaned, the silicon wafer is fixed on a coating table so that the trapezoidal groove area is completely exposed, and the titanium dioxide gel is evenly coated on the surface of the silicon wafer and in the trapezoidal grooves using a coating device. After coating, the titanium dioxide gel on the surface of the silicon wafer is cleaned, and the silicon wafer is placed in a vacuum drying oven and dried at 80°C-120°C for 15-30 minutes to evaporate the solvent in the titanium dioxide gel in the grooves to form a preliminary solidified titanium dioxide electrode.
[0015] Preferably, the dried silicon wafer is carefully placed in a high temperature furnace, and the temperature is gradually increased to 400°C-500°C at a rate of 2°C-5°C / min, and the constant temperature is maintained for 30-60 minutes to form a dense titanium dioxide electrode.
[0016] Preferably, the pretreatment in step 1 includes cleaning, texturing, PSG removal, diffusion, etching, surface activation, and pre-cleaning. Beneficial Effects
[0017] The present invention provides a process for preparing a composite electrode for a solar cell, which has the following beneficial effects: (1) This solar cell composite electrode preparation process forms a trapezoidal groove on the surface of a single crystal silicon wafer by laser etching, which has a large surface area and is conducive to the deposition and distribution of metal electrode materials (silver and copper). The physical vapor deposition method (PVD) can accurately control the deposition of silver and copper to ensure the uniformity of the material in the groove. The trapezoidal groove design can greatly increase the contact area of the electrode and improve the conductivity of the electrode. Compared with the traditional planar electrode structure, this design effectively reduces the contact resistance of the electrode and enhances the conductivity efficiency of the electrode. In particular, in devices such as solar cells, the current transmission efficiency is significantly improved.
[0018] (2) A process for preparing a composite electrode for a solar cell comprises depositing silver and copper in a trapezoidal groove to form a composite electrode. Silver has excellent electrical conductivity, and copper has strong mechanical strength. The combination of the two can enhance the stability of the electrode while improving the electrical conductivity. The silver-copper combination of the composite electrode has higher mechanical strength and corrosion resistance than a single metal electrode, and can effectively extend the service life of the electrode. In harsh environments (such as high temperature, humidity, etc.), the performance of the composite electrode is more stable, reducing the degradation of electrical performance due to material degradation.
[0019] (3) The preparation process of the composite electrode for solar cells. The titanium dioxide electrode layer has excellent light absorption ability. In particular, the three-dimensional structure formed in the trapezoidal grooves can increase the light capture efficiency and enhance the generation of photogenerated electrons. Compared with the traditional planar electrode, this design has greatly improved the photoelectric conversion efficiency and is particularly suitable for optoelectronic devices such as solar cells.
[0020] (4) In the preparation process of the composite electrode of a solar cell, after the trapezoidal groove is formed by laser etching, a suitable deposition process can be selected according to different electrode materials and application requirements. The physical vapor deposition method is suitable for the precise deposition of metal materials (such as silver and copper), while the scraping method is suitable for the uniform coating and structure formation of non-metallic materials (such as titanium dioxide) under specific conditions. This technology has high process flexibility and can select the most suitable electrode deposition method according to actual needs. This flexibility enables the process to adapt to different materials and device structures, expanding the application scope of the technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a flow chart of the present invention. DETAILED DESCRIPTION
[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Embodiment 1: A process for preparing a composite electrode for a solar cell, comprising the following steps: (1) Pretreatment of single crystal silicon wafers Cleaning: The monocrystalline silicon wafer needs to be thoroughly cleaned to remove particles, organic matter and metal impurities on the surface. This step usually uses APM solution and deionized water for spraying and circulating flushing to ensure the cleanliness of the silicon wafer surface.
[0024] Texturing: In order to increase light absorption, the surface of the silicon wafer needs to be texturized to form a pyramid-shaped texture. This step can be achieved through chemical treatment, such as using a mixed solution of hydrofluoric acid and nitric acid, or through physical methods such as sandblasting.
[0025] Removing PSG (phosphorus silicon glass): During the diffusion process, a layer of SiO2 will form on the surface of the silicon wafer. It is necessary to remove the N-type silicon at the edge through wet etching to insulate the upper and lower surfaces of the silicon wafer from each other and prevent PN junction short circuit.
[0026] Diffusion: At high temperatures, n-type or p-type regions are formed on the surface of the silicon wafer through a diffusion process, which is a key step in forming the pn junction of a solar cell.
[0027] Etching: After diffusion, wet etching is required to remove the phosphosilicate glass and porous silicon on the surface of the silicon wafer to reduce the recombination of electrons in the emission area, increase the electron life, and thus increase the open circuit voltage and short circuit current of the battery.
[0028] Surface activation: In some cases, it may be necessary to activate the silicon wafer surface to increase the surface energy and improve the adhesion of materials in subsequent processes.
[0029] Pre-cleaning: Prior to final processing, the wafer may also need to be pre-cleaned to remove any residues that may have been introduced during previous processing steps.
[0030] (2) Laser Grooving In order to achieve precise etching effect on single crystal silicon wafer, this embodiment uses ultra-short pulse ultraviolet (UV) laser. This type of laser can vaporize the material in a very short time, reduce the heat-affected zone, ensure that the etching area is clean and has no residue, and single crystal silicon has a high energy absorption rate for ultraviolet wavelength laser (such as 355nm), which can effectively perform high-precision etching.
[0031] During etching, bevel groove etching is performed first. The pre-cleaned single-crystal silicon wafer is placed horizontally on a precision moving table with the front side facing up. The inclination angle of the two sets of laser beams is set to 50°, and the wavelength of the laser is ensured to be 355nm, the pulse duration is in the picosecond level, the pulse frequency is set at around 100kHz, the single pulse energy is 50μJ-200μJ, and the focal length is adjusted to a focal diameter of 50μm-100μm to achieve fine and precise etching lines. The target etching depth is 5 microns. The two sets of laser beams scan the surface of the silicon wafer from different directions at the same time to ensure that the focus of the laser beam falls exactly on the same etching area to form a symmetrical bevel groove structure. The scanning speed is initially set to 30 microns / s and adjusted according to the etching effect. Since the etching depth is 5 microns, etching can be performed in multiple times to control the depth of each etching to be around 1 micron to reduce thermal damage and unevenness.
[0032] Vertical laser etching is then performed, with the wavelength still at 355nm, the initial power set to 60μJ, the pulse frequency adjusted to 150kHz, the target depth to 4 microns, the width to 10 microns, and the scanning path set to ensure that the laser beam performs vertical etching in the middle of the formed oblique groove, with the goal of merging the oblique grooves on both sides to form a trapezoidal structure.
[0033] The above are the etching grooves for preparing fine gates on the surface. The number can be determined according to the material. For example, 150 fine etching grooves are etched on a 200mm*200mm single crystal silicon wafer. When preparing the main gate, a wide groove with a top surface width of 60 microns is etched, and a total of 10 main grooves are prepared.
[0034] After etching is completed, the silicon wafer is immediately cooled by air flow or air cooling to avoid material damage caused by the heat-affected zone. Subsequently, deionized water or other cleaning agents are used to remove any tiny particles that may remain on the surface.
[0035] (3) Using physical vapor deposition to deposit metal wires in the grooves Before deposition, ensure that the etched silicon wafer is ultrasonically cleaned and dried to remove surface oxides and organic matter. Plasma cleaning can be used for further cleaning to ensure the surface is clean. The cleaned silicon wafer is facing up, and the designed mask and silicon wafer are fixed horizontally on the moving table or rotating fixture in the PVD equipment. The mask covers the area where deposition is not required, and only allows material to be deposited in the etched grooves.
[0036] Start the PVD equipment and gradually reduce the pressure in the vacuum chamber to 10 −6 Torr or less, ensuring that the deposition process is not affected by gas phase impurities, heating the substrate to the set temperature (100°C-150°C), improving the adhesion of silver and copper films, placing a silver target with a purity of 99.99% in an electron beam evaporator, adjusting the electron beam power to 5-10kW, allowing the silver target to gradually evaporate into gas phase silver atoms, and controlling the silver deposition rate at 2-10Å / s by monitoring the quartz crystal monitor. Observe the deposition of silver in the groove to ensure that silver is evenly covered on the bottom and side walls of the trapezoidal groove to avoid excessive accumulation outside the groove, and deposit a 1-micron thick silver film according to the design requirements.
[0037] Maintaining the vacuum environment, after stopping the silver evaporation, switch the evaporation source to the copper target, start the copper deposition process, change the electron beam power to 4-8kW, make the copper target evaporate evenly, control the copper deposition rate to be similar to that of silver, and keep it in the range of 2-10Å / s. Due to the high deposition temperature of copper, the substrate temperature can be slightly increased to 150°C-200°C to improve the crystal structure and film quality of copper. Deposit 1 micron copper film on the silver layer to form a composite electrode structure. Monitor the thickness in real time through the quartz crystal monitor to ensure that it is consistent with the design requirements.
[0038] In order to make the deposited silver and copper films fully and evenly deposited in the grooves with inclined surfaces during the deposition process, the rotation angle of the PVD equipment is rotated during the deposition process to perform multi-angle deposition. According to actual needs, the deposition thickness and sequence of silver and copper can be adjusted to optimize the conductivity and stability of the composite electrode. The silver layer provides excellent conductivity, while the copper layer can enhance mechanical strength and corrosion resistance. After deposition is completed, gradually lower the temperature of the substrate to prevent the film from cooling too quickly, causing stress concentration or cracking. Confirm that the composite electrode deposition is complete, stop the equipment, slowly vent to atmospheric pressure, and take the substrate out of the vacuum chamber. The deposited composite electrode can be annealed (temperature 300°C-400°C) to improve the crystal structure, conductivity and adhesion of the electrode.
[0039] Embodiment 2: A process for preparing a composite electrode for a solar cell, comprising the following steps: (1) Pretreatment of single crystal silicon wafers Cleaning: The monocrystalline silicon wafer needs to be thoroughly cleaned to remove particles, organic matter and metal impurities on the surface. This step usually uses APM solution and deionized water for spraying and circulating flushing to ensure the cleanliness of the silicon wafer surface.
[0040] Texturing: In order to increase light absorption, the surface of the silicon wafer needs to be texturized to form a pyramid-shaped texture. This step can be achieved through chemical treatment, such as using a mixed solution of hydrofluoric acid and nitric acid, or through physical methods such as sandblasting.
[0041] Removing PSG (phosphorus silicon glass): During the diffusion process, a layer of SiO2 will form on the surface of the silicon wafer. It is necessary to remove the N-type silicon at the edge through wet etching to insulate the upper and lower surfaces of the silicon wafer from each other and prevent PN junction short circuit.
[0042] Diffusion: At high temperatures, n-type or p-type regions are formed on the surface of the silicon wafer through a diffusion process, which is a key step in forming the pn junction of a solar cell.
[0043] Etching: After diffusion, wet etching is required to remove the phosphosilicate glass and porous silicon on the surface of the silicon wafer to reduce the recombination of electrons in the emission area, increase the electron life, and thus increase the open circuit voltage and short circuit current of the battery.
[0044] Surface activation: In some cases, it may be necessary to activate the silicon wafer surface to increase the surface energy and improve the adhesion of materials in subsequent processes.
[0045] Pre-cleaning: Prior to final processing, the wafer may also need to be pre-cleaned to remove any residues that may have been introduced during previous processing steps.
[0046] (2) Laser Grooving In order to achieve precise etching effect on single crystal silicon wafer, this embodiment uses ultra-short pulse ultraviolet (UV) laser. This type of laser can vaporize the material in a very short time, reduce the heat-affected zone, ensure that the etching area is clean and has no residue, and single crystal silicon has a high energy absorption rate for ultraviolet wavelength laser (such as 355nm), which can effectively perform high-precision etching.
[0047] During etching, bevel groove etching is performed first. The pre-cleaned single-crystal silicon wafer is placed horizontally on a precision moving table with the front side facing up. The inclination angle of the two sets of laser beams is set to 50°, and the wavelength of the laser is ensured to be 355nm, the pulse duration is in the picosecond level, the pulse frequency is set at around 100kHz, the single pulse energy is 50μJ-200μJ, and the focal length is adjusted to a focal diameter of 50μm-100μm to achieve fine and precise etching lines. The target etching depth is 5 microns. The two sets of laser beams scan the surface of the silicon wafer from different directions at the same time to ensure that the focus of the laser beam falls exactly on the same etching area to form a symmetrical bevel groove structure. The scanning speed is initially set to 30 microns / s and adjusted according to the etching effect. Since the etching depth is 5 microns, etching can be performed in multiple times to control the depth of each etching to be around 1 micron to reduce thermal damage and unevenness.
[0048] Vertical laser etching is then performed, with the wavelength still at 355nm, the initial power set to 60μJ, the pulse frequency adjusted to 150kHz, the target depth to 4 microns, the width to 10 microns, and the scanning path set to ensure that the laser beam performs vertical etching in the middle of the formed oblique groove, with the goal of merging the oblique grooves on both sides to form a trapezoidal structure.
[0049] The above are the etching grooves for preparing fine gates on the surface. The number can be determined according to the material. For example, 150 fine etching grooves are etched on a 200mm*200mm single crystal silicon wafer. When preparing the main gate, a wide groove with a top surface width of 60 microns is etched, and a total of 10 main grooves are prepared.
[0050] After etching is completed, the silicon wafer is immediately cooled by air flow or air cooling to avoid material damage caused by the heat-affected zone. Subsequently, deionized water or other cleaning agents are used to remove any tiny particles that may remain on the surface.
[0051] (3) The titanium dioxide gel is evenly coated in the trapezoidal grooves of the laser-etched single-crystal silicon wafer and burned to form a stable titanium dioxide electrode. Mix titanium dioxide powder with an appropriate amount of solvent (such as ethanol, water) and dispersant to form a stable titanium dioxide colloidal solution. Ensure that the viscosity of the colloid is suitable for scraping. Use high-speed stirring or ultrasonic treatment to evenly disperse the titanium dioxide particles in the solution to prevent particle agglomeration and ensure that a uniform film is formed after coating.
[0052] Clean the laser-etched single-crystal silicon wafer to remove dust and residue on the surface, blow dry the silicon wafer with nitrogen or dry it in a vacuum drying oven, and fix the silicon wafer on a scraping table to ensure that its surface is level, especially the trapezoidal groove area is fully exposed.
[0053] Use a scraper to evenly coat the titanium dioxide gel on the surface of the silicon wafer. Pay attention to adjusting the thickness control device of the scraper to ensure that the colloid can evenly enter the trapezoidal grooves. After coating, clean the titanium dioxide gel on the surface of the silicon wafer and place the silicon wafer in a vacuum drying oven at 80°C-120°C for 15-30 minutes to evaporate the solvent in the titanium dioxide gel in the grooves to form preliminary solidified titanium dioxide.
[0054] Carefully place the dried silicon wafer into a high-temperature furnace, ensuring that the surface of the silicon wafer is not scratched or damaged, and gradually increase the temperature to 400°C-500°C at a rate of 2°C-5°C / min. Slow heating helps reduce the internal stress of the titanium dioxide layer and prevent the titanium dioxide grid from cracking. When the temperature reaches the set value, keep the constant temperature for 30-60 minutes to ensure that the titanium dioxide grid is completely sintered to form a dense titanium dioxide electrode.
[0055] After sintering is completed, the temperature is slowly lowered to room temperature. Avoid rapid cooling to prevent stress cracks in the material. When the temperature returns to a safe range, the substrate is removed from the furnace. At this point, the titanium dioxide electrode has been formed in the trapezoidal groove.
[0056] During the preparation process, the titanium dioxide gel has an appropriate viscosity to ensure that the trapezoidal grooves can be evenly covered when knife-coated without flowing or collapsing.
[0057] The combination of scraping and laser etching to form trapezoidal grooves can ensure that the titanium dioxide material accurately fills the grooves to form a high surface area electrode, which helps to improve the performance of the electrode.
[0058] The sintering process of slowly heating up and cooling down can completely remove the organic matter in the titanium dioxide gel, ensuring the final formation of a dense and highly conductive titanium dioxide electrode.
[0059] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A process for preparing a composite electrode for a solar cell, comprising the following steps: S1: Pretreatment of single crystal silicon wafers; S2: Laser inclined groove forming a groove that is wide inside and narrow outside; S3: Filling the precursor into the groove to form a composite electrode.
2. The process for preparing a composite electrode for a solar cell according to claim 1, characterized in that: In step 2, at least one set of tilted lasers is used to etch the monocrystalline silicon wafer on the opposite side. The laser tilt angle is set to 50°, the wavelength is 355nm, the pulse duration is in the picosecond level, the pulse frequency is set to 100kHz, the single pulse energy is 50μJ-200μJ, the focal length is adjusted to a focal diameter of 50μm-100μm, the target etching depth is 5 microns, and the scanning speed is initially set to 30 microns / s.
3. The process for preparing a composite electrode for a solar cell according to claim 2, characterized in that: The single crystal silicon wafer etched with inclined grooves is etched using a laser perpendicular to the single crystal silicon wafer, with a target depth of 4 microns and a width of 10 microns, generating a rectangular groove, which together with the inclined groove forms a trapezoidal groove.
4. The process for preparing a composite electrode for a solar cell according to claim 1, characterized in that: In step 3, the precursors are silver and copper, and the silver and copper are deposited in the grooves by physical vapor deposition to form a composite electrode.
5. The process for preparing a composite electrode for a solar cell according to claim 1, characterized in that: In step 3, the precursor is titanium dioxide gel, which is evenly scraped onto the trapezoidal grooves of the laser-etched single-crystal silicon wafer, and then burned to form a stable titanium dioxide electrode.
6. The process for preparing a composite electrode for a solar cell according to claim 4, characterized in that: The designed mask and the etched silicon wafer are fixed horizontally on the rotating fixture in the PVD equipment. The pressure of the vacuum chamber of the PVD equipment is reduced to 10 −6 Torr, heat the substrate of the PVD equipment to 100°C-150°C, adjust the electron beam power of the electron beam evaporator to 5-10kW, and control the silver deposition rate to 2-10Å / s by monitoring the quartz crystal monitor to form a silver coating.
7. The process for preparing a composite electrode for a solar cell according to claim 6, characterized in that: After stopping silver evaporation, switch the evaporation source to a copper target, adjust the electron beam power of the electron beam evaporator to 4-8kW, keep the deposition rate within the range of 2-10Å / s, and increase the substrate temperature of the PVD equipment to 150°C-200°C.
8. The process for preparing a composite electrode for a solar cell according to claim 5, characterized in that: The laser-etched single crystal silicon wafer is cleaned, and the silicon wafer is fixed on a coating table to fully expose the trapezoidal groove area. The titanium dioxide gel is evenly coated on the surface of the silicon wafer and in the trapezoidal groove using a coating device. After coating, the titanium dioxide gel on the surface of the silicon wafer is cleaned, and the silicon wafer is placed in a vacuum drying oven and dried at 80°C-120°C for 15-30 minutes to evaporate the solvent in the titanium dioxide gel in the groove to form a preliminary solidified titanium dioxide electrode.
9. The process for preparing a composite electrode for a solar cell according to claim 8, characterized in that: Carefully place the dried silicon wafer into a high-temperature furnace, gradually heat it to 400-500°C at a rate of 2-5°C / min, and maintain the constant temperature for 30-60 minutes to form a dense titanium dioxide electrode.
10. The process for preparing a composite electrode for a solar cell according to claim 1, characterized in that: The pretreatment in step 1 includes cleaning, texturing, PSG removal, diffusion, etching, surface activation, and pre-cleaning.